2004
DOI: 10.1002/lsm.20090
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral thermal and mechanical damage to dentin with microsecond and sub‐microsecond 9.6 μm, 2.79 μm, and 0.355 μm laser pulses

Abstract: High resolution SR-FTIR is well suited for characterization of the chemical changes that occur due to thermal damage peripheral to laser incisions in proteinaceous hard tissues. Sub-microsecond pulsed IR lasers resonant with water and mineral absorption bands ablate dentin efficiently with minimal thermal damage. Similar laser parameters are expected to apply to the ablation of alveolar bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 31 publications
2
42
1
1
Order By: Relevance
“…In the mid-infrared range, specifically at wavelengths that are strongly absorbed by dental hard tissue, microsecond pulses likely require less water cooling to prevent peripheral thermal damage. 31 The pulse width applied in the present study (5 ns) is significantly shorter than the thermal diffusion time of carious dentin, so it is expected to incur minimal thermal damage and allow less water spray.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the mid-infrared range, specifically at wavelengths that are strongly absorbed by dental hard tissue, microsecond pulses likely require less water cooling to prevent peripheral thermal damage. 31 The pulse width applied in the present study (5 ns) is significantly shorter than the thermal diffusion time of carious dentin, so it is expected to incur minimal thermal damage and allow less water spray.…”
Section: Discussionmentioning
confidence: 96%
“…[4][5][6][7] Excellent high-speed precise ablation of dental caries has been achieved by pulsed CO 2 lasers with the wavelengths of 9.6 and 9.3 μm. [25][26][27][28][29][30][31] Dental target selectivity using CO 2 lasers, Nd:YAG laser, and lasers with the wavelengths of 355, 377, and 400 nm has also been reported. [32][33][34][35][36] The present study of selective laser-based ablation for carious dentin is entirely novel.…”
Section: Discussionmentioning
confidence: 99%
“…Specific laser conditions were chosen for this study that have been found to produce minimal thermal modification of the dentin 22 . Laser irradiation can induce changes in the birefringence and roughness of the dentin surface that may interfere with the ability of PS-OCT to assess the lesion severity.…”
Section: Introductionmentioning
confidence: 99%
“…Picosecond lasers have been tested, but enamel or dentine cracking has been observed (Lizarelli et al 1999, Swift et al 2001, Niemz 1998. Lasers with nanosecond pulses may or may not induce significant thermal or mechanical damage, depending on the wavelength (Patel et al 1994, Lee et al 2000, Papagiakoumou et al 2004, Dela Rosa et al 2004. The most promising laser with nanosecond pulse duration has a wavelength of 193 nm which causes very little thermal and mechanical damage to teeth because the main mechanism of ablation has a photochemical nature.…”
Section: Introductionmentioning
confidence: 99%